Antibiotics in livestock wastewater treatment by using biomass-derived activated carbon supported ZnS nanomaterials - Luo, Qi (Water science and technology : a journal of the International Association on Water Pollution Research, 2019)
A new type of composite photocatalyst material was successfully prepared through the ultrasound-assisted coprecipitation method precipitate of zinc sulfide (ZnS) nanomaterials on peach wood activated carbon (PAC). The optimization of ZnSPAC demonstrates excellent photocatalytic performance by using the response surface method (RSM), which is essential for improving photocatalytic performance. In this model it was found that the photocatalytic degradation of enrofloxacin (ENR) increased with microwave heating power and ZnS concentration, whereas it decreased with increasing activation time. The RSM model predicts that under certain conditions (microwave heating power 800 W, activation time 3 h, ZnS 0.5 mol·L-1), the maximum degradation rate of ENR in livestock and poultry wastewater is 97.81%. By empirical testing under the optimum conditions with 97.35% degradation the accuracy of the designed model was proven using RSM and the mechanism of the photocatalytic process was studied